The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.5694/j.1326-5377.1999.tb126889.x
|View full text |Cite
|
Sign up to set email alerts
|

Vascular dementia: diagnosis, management and possible prevention

Abstract: There has been a recent upsurge of interest in the clinical features of and risk factors for vascular dementia, and consensus is emerging on its diagnostic characteristics. We discuss these features and risk factors and the main intervention strategies, both for treatment and prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 19 publications
1
38
0
2
Order By: Relevance
“…Distribution of cognitive performances confirmed that attention-executive dysfunction is one of the prominent features of subcortical vascular cognitive impairment (VCI) [6,7,33]. Impairment in high level visuo-constructional abilities was also observed in our sample.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Distribution of cognitive performances confirmed that attention-executive dysfunction is one of the prominent features of subcortical vascular cognitive impairment (VCI) [6,7,33]. Impairment in high level visuo-constructional abilities was also observed in our sample.…”
Section: Discussionsupporting
confidence: 79%
“…This damage of the frontal lobe is reflected in the fact that alteration in executive and attentional processing seems to be the core feature of subcortical VaD; these patients are grossly slowed up with poor information retrieval and problems with tasks that require mental flexibility and shifting of attention [7]. Executive and attentional abilities are critical to the daily functioning and have important consequences on the patient's social adjustment and maintenance of independence in a complex society.…”
Section: Introductionmentioning
confidence: 99%
“…The decline in cognitive and especially global function in placebo-treated AD patients is consistent with the progressive and unremitting nature of this disease. It is in contrast with the situation in patients with VaD, who often exhibit a sudden onset of symptoms and may be stable for some time before suffering stepwise decline [22], usually linked to the occurrence of a cerebrovascular event. Similar placebo group behaviors have been reported in a previous study that compared VaD and AD patient characteristics [23].…”
Section: Discussionmentioning
confidence: 76%
“…Subcortical ischemic vascular disease caused by small vessel disease (SVD) has been shown to be closely associated with cognitive impairment [6,7], particularly with deficits in attention and executive function, and slowing of motor performance and information processing [8][9][10]. The clinical spectrum of vascular cognitive impairment (VCI) ranges from MCI to dementia [6] and a recent proposal of diagnostic criteria for vascular MCI highlights the need of an objective evidence of decline using validated measures of cognitive functions and giving equal importance to several cognitive domains [11].…”
Section: Introductionmentioning
confidence: 99%